Autoantigen Discovery in the Hair Loss Disorder, Alopecia Areata: Implication of Post-Translational Modifications - Jadeja, Shahnawaz D.; Tobin, Desmond J. (Frontiers in Immunology, 2022)
Alopecia areata (AA) is a chronic, multifactorial, polygenic, and heterogeneous disorder affecting growing hair follicles in susceptible individuals, which results in a non-scarring and reversible hair loss with a highly unpredictable course. Despite very considerable research effort, the nature of the precipitating factor(s) responsible for initiating AA in any given hair follicle remains unclear, due largely to significant gaps in our knowledge of the precise sequence of the etiopathogenic events in this dermatosis. However, disease-related changes in the immune-competence of the lower growing hair follicle, together with an active immune response (humoral and cellular) to hair follicle-associated antigens, are key associated phenomena. Confirmation of the hair follicle antigen(s) implicated in AA disease onset has remained stubbornly elusive. While it may be considered somewhat philosophical by some, it is also unclear whether immune-mediated hair loss in AA results from a) an ectopic (i.e., in an abnormal location) immune response to native (unmodified) self-antigens expressed by the healthy hair follicle, b) a normal immune response against modified self-antigens (or neoantigens), or c) a normal immune response against self-antigens (modified/non-modified) that were not previously visible to the immune system (because they were conformationally-hidden or sequestered) but become exposed and presentable in an MHC-I/-II molecule-restricted manner. While some candidate hair follicle antigen target(s) in AA are beginning to emerge, with a potential role for trichohyalin, it is not yet clear whether this represents the initial and immunodominant antigenic focus in AA or is simply one of an expanding repertoire of exposed hair follicle tissue damage-associated antigens that are secondary to the disease. Confirmation of autoantigen identity is essential for our understanding of AA etiopathogenesis, and consequently for developing a more informed therapeutic strategy. Major strides have been made in autoantigen discovery in other autoimmune conditions. In particular, some of these conditions may provide insights into how post-translational modifications (e.g., citrullination, deamidation, etc.) of hair follicle-restricted proteins may increase their antigenicity and so help drive the anti-hair follicle immune attack in AA.